Novel Inhibitors of Acetyl- and Butyrylcholinesterase Derived from Benzohydrazides: Synthesis, Evaluation and Docking Study - Houngbedji, Neto-Honorius; Štěpánková, Šárka; Pflegr, Vaclav; Svrčková, Katarína; Svarcova, Marketa; Vinsova, Jarmila; Kratky, Martin (MDPI, 2023)
On the basis of previous reports, novel 2-benzoylhydrazine-1-carboxamides were designed as potential inhibitors of acetylcholinesterase (AChE) and butyrylcholinesterase (BChE). Inhibitors of these enzymes have many clinical applications. 2-(Substituted benzoyl)hydrazine-1-carboxamides decorated with N-methyl or tridecyl were prepared with three methods from commercially available or self-prepared hydrazides and isocyanates. For methyl derivatives, N-succinimidyl N-methylcarbamate was used or methyl isocyanate was prepared via Curtius rearrangement. Tridecyl isocyanate was synthesized again via Curtius rearrangement or from triphosgene and tridecylamine. The compounds were evaluated for the inhibition of AChE and BChE using Ellman's spectrophotometric method. Most of the derivatives showed the dual inhibition of both enzymes with IC50 values of 44-100 mu M for AChE and from 22 mu M for BChE. In general, the carboxamides inhibited AChE more strongly. A large number of the compounds showed better or quite comparable inhibition of cholinesterases in vitro than that of the drug rivastigmine. Molecular docking was performed to investigate the possible conformation of the compounds and their interactions with target enzymes. In both AChE and BChE, the compounds occupied the enzyme active cavity, and, especially in the case of BChE, the compounds were placed in close proximity to the catalytic triad.
Nové inhibitory acetyl- a butyrylcholinesterázy odvozené od benzohydrazidů: Syntéza, hodnocení a studie dokování
Keywords: acetylcholinesterase; benzohydrazide; butyrylcholinesterase; hydrazine-1-carboxamide; enzyme inhibition; molecular docking; acetylcholinesteráza; benzohydrazid; butyrylcholinesteráza; hydrazin-1-karboxamid; inhibice enzymů; molekulární dokování